Prinsip Proporsionalitas dan Kebebasan Berekspresi dalam Kitab Undang-Undang Hukum Pidana (KUHP) Revisi Indonesia: Sebuah Analisis Demokrasi Deliberatif - Tahir, Muh. Taqwin; Yanlua, Muh. Akbar; Lawung, Mario Aprio Almit (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2026)
This article examines the regulation of freedom of expression in Indonesia's new Criminal Code with a focus on insults to the President/Vice President, insults to state institutions, and provisions on unrest and fake news that have the potential to limit the space for criticism and public discourse. The main issue raised is whether the configuration of the restrictions is in line with the principle of proportionality and how its implications are for the quality of deliberative democracy in Indonesia. In particular, the article links the constitutional guarantee of freedom of expression in the 1945 Constitution and international law with the design and potential application of new articles of the Criminal Code that touch on the realm of political expression and expression in the digital space. This research uses normative legal methods with legislative, conceptual, and case approaches, based on an analysis of the 1945 Constitution, international law, laws, Constitutional Court decisions, and the latest literature on freedom of expression, the principle of proportionality, and deliberative democracy. The principle of proportionality is applied to assess the extent to which restrictions in the new Criminal Code are justifiable in a democratic society. The results of the study show that, although formally meeting the requirements for restrictions through the law, a number of new articles of the Criminal Code have the potential to close discursive spaces that are oriented towards excessive protection of state officials and institutions, as well as ignore the availability of non-criminal instruments that are less intrusive, thus failing to meet the test of necessity and nonexcessiveness. This configuration has implications for the strengthening of the chilling effect and self-censorship in the public space, which in turn reduces the quality of democracy in Indonesia. The article recommends normative correction through testing in the constitutional court and revision of the law to be in harmony with the ideals of a democratic state of law.